Don't be trashy : a practical guide to living with less waste and more joy - McKenna, Tara (Rodale, 2022)
"We're all trapped in a convenience-based and wasteful cycle, but Tara McKenna offers an alternative: an approach to reducing waste for a more sustainable and ethical life that emphasizes progress over perfection. This isn't about fitting all of your waste into a Mason jar or going zero waste overnight. For real, long-lasting change that will enhance your life, McKenna guides you through a year of reducing waste, month by month, with lifestyle topics ranging from decluttering and developing a capsule wardrobe to streamlining your kitchen, pantry, and bathroom--slowly!--to significantly reduce the inflow of single-use plastics. This is an opportunity to become a more conscious consumer, as McKenna emphasizes the importance of a circular economy, and soon you'll be investing in home goods that'll last for decades. Ultimately, it's about transitioning to a minimalist mindset--a mindset that, coincidentally, will be good for your wallet--and the planet--in the long term"--